Comparative analysis of nitrifying bacteria in full-scale oxidation ditch and aerated nitrification biofilter by using fluorescent in situ hybridization (FISH) and denaturing gradient gel electrophoresis (DGGE) - ÇALLI, BARIŞ; MERTOĞLU, BÜLENT (My University, 2005)
In this study, nitrification performances and composition of nitrifying populations in a full-scale oxidation ditch and a high-rate submerged media nitrification biofilter were comparatively analyzed. In addition to different reactor configurations, effects of differing operational conditions on the nitrification efficiency and bacterial diversity were also explored and evaluated thoroughly. In microbial analysis of sludge samples fluorescent in situ hybridization (FISH) and denaturing gradient gel electrophoresis (DGGE) techniques were used complementary to each other. The extended aeration oxidation ditch subjected to the study is operated as a nitrogen and phosphorus removal system consisting of anaerobic, anoxic, and aerobic zones. The high-rate submerged media aerated filter is operated as nitrification step following the conventional activated sludge unit and the nitrified wastewater is discharged to the sea without complete nitrogen removal. In situ hybridization results have indicated that Nitrosomonas-like ammonia oxidizing and Nitrospira-related nitrite oxidizing bacteria were intensively present in vigorous flocs in nitrification biofilter while carbonaceous bacteria belong to beta subclass of Proteobacteria were considerably dominant in oxidation ditch. Low quantities of nitrifiers in oxidation ditch were also confirmed by the dissimilarity in intensive bands between two systems obtained with DGGE analysis.
Keywords: DNA, Bacterial; Biofilms; Polymerase Chain Reaction; Nitrites; Oxidation-Reduction; Waste Disposal, Fluid; Ammonia; Electrophoresis, Gel, Pulsed-Field; In Situ Hybridization, Fluorescence; Sewage; Aerobiosis; Proteobacteria